Early detection of cerebral palsy in high-risk infants: diagnostic value of primitive and developmental reflexes as well as ultrasound - Setyo Handryastuti; Ghaisani Fadiana; Sofyan Ismael; Sudigdo Sastroasmoro; Asril Aminulah; Ferial Hadipoetro Idris; Adji Saptogino; Sunartini Hapsara (Indonesian Pediatric Society, 2018)
Background The incidence of cerebral palsy (CP) has increased due to better survival of high-risk babies. A simple assessment method is needed for the early detection of CP, which can be performed by general practitioners and pediatricians in daily practice.Objectives To assess motor delay, primitive and developmental reflexes, and cerebral ultrasound abnormalities as simple methods for early detection of CP in high-risk infants. We also aimed to evaluate the ease and consistency of the methods for use in daily practice, as well as determine risk factors associated with CP.Methods A prospective cohort study was done on 150 high-risk babies starting from the age of 4 months up to 12 months. We obtained subjects’ histories of motor ability and assessed primitive reflexes and postural reactions at the ages of 4, 6, 9 and 10 months. The diagnosis of CP was established at 6 and 12 months of age. We also determined Kappa test for inter-rater reliability between pediatric residents and pediatric neurologist.Results In 88.7% of subjects, CP was detected in the first 6 months. At 4 months, positive palmar reflex, head lag, and fisting were predictive of CP at 6 months of age. Motor delay, positive palmar grasp reflex, head lag, fisting, and absent protective extension reflex at 6 months were predictive of CP at 12 months. At 9 to 10 months, motor delays, absent protective extension reflex, and negative parachute reaction were predictive of CP at 12 months. Cerebral ultrasound abnormalities were predictive of CP at 6 and 12 months of age. Kappa test result was 0.9, indicating the ease and consistency of these methods for daily medical practice.Conclusion Cerebral palsy can be detected as early as the first 6 months of life. Assessment for motor delays, physical examination for asssessing primitive and developmental reflexes, and cerebral ultrasound can be used for this purpose.